2015
DOI: 10.1002/imhj.21528
|View full text |Cite
|
Sign up to set email alerts
|

Personal Competencies, Social Resources, and Psychosocial Adjustment of Primiparous Women of Advanced Maternal Age and Their Partners

Abstract: The present study aimed to (a) characterize the personal competencies, the social resources, and the psychosocial adjustment (psychological distress, quality of life, and parenting self-perceptions) during the early postpartum period of primiparous women of advanced age (≥35 years at the time of delivery) and their partners (older parents) compared with that of younger first-time mothers (20-34 years) and their partners (younger parents); and (b) explore the role of personal competencies and social resources i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Similar to depression, no changes were observed in perceived social support, which was high at both assessment times. This is an important finding considering that social support seems to have a buffering effect on women's health during the perinatal stage and, as some authors affirm, social support could contribute to reducing the impact of stress and depressive symptomatology [48]. Related to this, the fact that in the present study baseline support from family and friends was prospectively associated with reduced depressive symptomatology is consistent with the idea that social support facilitates the journey to motherhood [53].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to depression, no changes were observed in perceived social support, which was high at both assessment times. This is an important finding considering that social support seems to have a buffering effect on women's health during the perinatal stage and, as some authors affirm, social support could contribute to reducing the impact of stress and depressive symptomatology [48]. Related to this, the fact that in the present study baseline support from family and friends was prospectively associated with reduced depressive symptomatology is consistent with the idea that social support facilitates the journey to motherhood [53].…”
Section: Discussionsupporting
confidence: 90%
“…Finally, multivariate regression was carried out to explore to what extent the changes in study outcomes (i.e., depressive symptoms, adjustment, and perceived social support) at Time 2 (third trimester of pregnancy) were explained by personality factors, after controlling for important covariates (i.e., age the corresponding outcome at Time 1, that is during the second trimester of pregnancy). Age was included as a covariate because it has been related to psychosocial adjustment during the perinatal period in the literature [48]. A Holm-Bonferroni correction was used for all statistical analyses, which resulted in a p-value of 0.0125.…”
Section: Discussionmentioning
confidence: 99%
“…This result reflects the dichotomy of parenting that Berry and Jones (1995) expected that the PSS would capture. In spite of these data needing further research, previous studies reported that older parents may experience increased fatigue and more professional responsibilities but also more positive parenting self-perceptions and higher self-confidence, when compared to younger couples (Guedes and Canavarro, 2015). Additionally, this group of parents reported the higher number of children in the family when compared to younger couples, which increases the demands on parents' resources (Baker et al, 2001).…”
Section: Discussionmentioning
confidence: 92%
“…The sample size in the included studies ranged from 30 to 5079 participants, with a mean of 507 participants. There were no studies conducted on only fathers, and only four studies (7%) included couples [ 25 , 37 39 ]. About half of the studies assessed QoL during pregnancy and half during the postpartum period.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five (58%) of these studies reported Cronbach’s alpha for all dimensions of the instrument separately. Three (7%) studies reported Cronbach’s alpha for the total scale: QOLS [ 81 ], MAPP-QOL [ 111 ], EUROHIS-QoL-8 [ 39 ]. And three (7%) studies reported Cronbach’s alpha for the component summary scores: SF-36 [ 58 ] and SF-12 [ 71 , 72 ].…”
Section: Resultsmentioning
confidence: 99%